Successful Treatment of Refractory Candidal Granuloma by Itraconazole and Terbinafine in Combination with Hyperthermia and Cryotherapy - Heli Yang; Xiaoxi Xu; Xin Ran; Yuping Ran (Dermatology and Therapy, 2020)
Abstract Candidal granuloma is a rare and refractory disease in clinical practice, usually reported in immunocompromised patients. We report a 57-year-old man who presented with candidal granuloma caused by Candida tropicalis. The diagnosis was confirmed according to histopathology and molecular identification. Prolonged duration of initial antifungal therapy did not obtain satisfactory improvement. Finally, the refractory disease was successfully treated by itraconazole and terbinafine in combination with hyperthermia and cryotherapy. The “blackish-red dot” dermoscopic sign of the verrucous granuloma gradually resolved during the treatment.